The Impacts of Direct, Indirect, and Metalinguistic Feedback Strategies on Iraqi Students’ Writing Performance in EGP Courses - Mohammad Zohrabi; Nava Nourdad; Israa Abbas Alsaadi (Journal of Modern Research in English Language Studies, 2025)
Recent research has focused on Written Corrective Feedback (WCF) as a viable approach to the instruction of second language writing that enables learners to self-correct their written output. The present study strived to determine the use of various WCF strategies in English for General Purposes (EGP) courses. Accordingly, it used a mixed-methods design to examine the utility of WCF in foreign language context of Iraq. To this end, in the quantitative phase, the researchers selected 104 intermediatelevel nursing students in four EGP classes of a public university in Iraq as the participants. Then, they assigned the learners to three experimental groups including direct, indirect, and metalinguistic groups and a control group. In addition, in the qualitative phase, the researchers randomly selected 10 students in each of the experimental groups and probed their perspectives on their relevant treatment using a researcher-developed semi-structured interview protocol. Additionally, the researchers used paired-samples t-test and one-way ANOVA to perform the data analysis in SPSS 25. Lastly, they took advantage of thematic analysis for analyzing the qualitative data of the study. Based on the results, all of the examined WCF strategies ameliorated nursing students’ writing performance. However, direct and metalinguistic WCF strategies were more efficacious than the indirect strategy. Moreover, the qualitative findings indicated that the participants had a preference for direct and metalinguistic WCF strategies. The results can have practical implications regarding the use of WCF strategies in Iraqi context.